Online teaching and learning materials enhancement workshop / Nurul Aityqah Yaacob, Nadiah Mohamed and Nor Ashikin Sahrom - Yaacob, Nurul Aityqah; Mohamed, Nadiah; Sahrom, Nor Ashikin (Universiti Teknologi MARA, Negeri Sembilan, 2022)
The Online Teaching and Learning Materials Enhancement Workshop was organized by the Faculty of Computer Science & Mathematics (FSKM), UiTM Negeri Sembilan Kampus Kuala Pilah from June 1 to June 2, 2022. During this session, we will be concentrating on the development of the materials for the Massive Open Online Course (MOOC) for MAT016. On that day, lecturers who were participating in the development of this MOOC were given step-by-step instructions on how to stage their planning and implementation of the project. A number of different programmes, including Quizizz, Proprofs, Plickers, Edpuzzle, Wordwall, and Genially, are utilized by content developers during the process of material preparation. The first and second sessions were facilitated by Norul Fadhilah Ismail and Mahfuzah Mahayadin, lecturers from Mathematics Department.